2014
DOI: 10.1186/1471-2393-14-225
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing support of postnatal transition in term infants after c-section

Abstract: BackgroundWhereas good data are available on the resuscitation of infants, little is known regarding support of postnatal transition in low-risk term infants after c-section. The present study was performed to describe current delivery room (DR) management of term infants born by c-section in our institution by analyzing videos that were recorded within a quality assurance program.MethodsDR- management is routinely recorded within a quality assurance program. Cross-sectional study of videos of term infants bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
2
12
0
2
Order By: Relevance
“…We have recently described great variations concerning the time needed for IV-placement in term newborns [22]. The present study shows similar results for preterm infants.…”
Section: Discussionsupporting
confidence: 87%
“…We have recently described great variations concerning the time needed for IV-placement in term newborns [22]. The present study shows similar results for preterm infants.…”
Section: Discussionsupporting
confidence: 87%
“…Konstantelos et al 7 recently reported that 25% of term infants delivered by C-section received some form of respiratory support in the delivery room. This, and the sixfold increase in the use of positive pressure support following the revision of neonatal guidelines reported by Hishikawa et al, 1 raises the question if all these infants would have only recovered with such support, or may these high rates also reflect a trend towards overtreatment?…”
mentioning
confidence: 99%
“…The section of the recorded image was chosen in such a way as to hide the identity of the caretaker. In the present study, all recordings of planned c-section of term and preterm infants born between January 2012 and April 2013 were analyzed [11,12].…”
Section: Video Recording and Analysismentioning
confidence: 99%
“…The video analysis of the recorded videos was performed using the software Interact (Mangold International GmbH, Arnstorf, Germany), an observation-based software [11,12]. Analysis started with the arrival of the newborn at the reanimation table.…”
Section: Video Recording and Analysismentioning
confidence: 99%
See 1 more Smart Citation